Relationship between maize and groundnut consumption and aflatoxin levels in Nepalese pregnant women eating a rice-dominated diet. - Andrews -Trevino Johanna; Webb Patrick; Shively Gerald; Rogers Beatrice; Baral Kedar; Davis Dale; Paudel Krishna; Pokharel Ashish; Shrestha Robin; Wang Jia-Sheng; Ghosh Shibani. (Tufts University. Tisch Library., 2018)
American Society of Nutrition 2018 presentation on Aflatoxin levels in Nepalese pregnant women eating rice dominated diet.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy